Technology Landscape for Surveying and Mapping in Construction Industry - Hidayat, F.; Arifin, A.; Farrosi, M. A. A.; Soemardi, B. W.; Pradoto, R. G. K.; Puri, E. R. (International Journal of Integrated Engineering, 2022)
Over time, the construction industry has faced many challenges: by 2030, it’s estimated that the number of construction projects will increase by 85%, but on the other hand, projects must be highly productive but efficient. These challenges often arise from how the construction industry able to capitalize technology and its willingness as well as ability to respond new technology. To provide a comprehensive view on how the technology is evolving the construction, a construction technology landscape is needed. The technological landscape is conducive to solving current problems and anticipating future needs. The study includes the collection and analysis of data through literature studies, as well as through surveys to construction practitioners in the industry. This study shows that although it has been applied since the 15th century, the utilization and development of survey and mapping technology in Indonesia is still quite far behind the construction industry in other countries. The result of the survey shows that although development of this technology is quite far behind the development of the world, the industry adaptation to survey and mapping technology in Indonesia has experienced quite significant developments. Currently, advanced technology (hardware and software) is increasingly used in various construction projects in Indonesia.